Hemihyperplasia with Multiple intestinal Lipomatosis presenting with intestinal obstruction due to intussusception, challenges in treatment- A Rare case - Malik, Pushpendra; Garg, Mahinder K (Asian Journal of Medical Sciences, 2021)
Hemihyperplasia is a syndrome with overgrowth of limbs and associated with various genomic syndromes. Rarely patient presents with intestinal obstruction when it is associated with sub mucosal lipomas. Submucosal lipomas are common in colon. But whole of small and large bowel studded with them is very rare as in our case. It presents dilemma not only in diagnosis but in treatment also. Here we present a case of forty two years females with hemihyperplasia syndrome came to causality with recurrent intestinal obstruction. On CECT Abdomen diagnosis of intestinal obstruction due to intussusception was made. Whole of bowel is studded with submucosal lipomas. Patient was tried to manage conservatively but patient does not respond and Right Hemicolectomy was done of intussusception segment. Anastomosis leaked and on re-exploration end ileostomy was done. Obstruction due to Multiple Intestinal Lipomatosis (as a part of Genetic Syndrome) should be managed conservatively and if operative intervention is required avoid primary anastomosis.